Dynamic Mechanical Analysis of Rubber Mixtures filled by Carbon Nanotubes - Bakosova, Dana (Manufacturing Technology Journal, 2018)
In this paper we observe dynamic mechanical properties of rubber mixtures - standard and CNT, where in the mixture CNT were dispersed nanoparticles - shape of carbon nanotubes (CNT). We used the testes apparatus by PerkinElmer ``PYRIS Diamond Dynamic Mechanical Analyzer'' for measuring mechanical properties. Dynamic mechanical analysis (DMA) is a technique used to study and characterize materials. It is the most useful for studying the viscoelastic behavior of polymers. A sinusoidal stress is applied and the strain in the material is measured, allowing one to determine the complex modulus. The temperature of the sample and the frequency of the stress are often varied, leading to variations in the complex modulus. Dynamic mechanical properties of tested mixtures are evaluated using frequency and thermal dependence. Dynamical tensile test we did during temperature program from 20 °C to 100 °C. We gradually applied frequencies 0.01 Hz, 0.5 Hz, 1 Hz, 10 Hz, 20 Hz and 50 Hz.
Keywords: DMA; Nanofillers; Storage Modulus; Loss Modulus; Complex Modulus